The role of paediatric point-of-care ultrasound in Spain: Present status and future perspectives - Ortiz-González, Luis; Ortiz-Peces, Luis; Ortiz-Peces, Carlos (The Ultrasound Journal, 2026)
Introduction: The use of ultrasound by physicians not specialized in diagnostic radiology, as an adjunct to physical examination, has been termed "point-of-care ultrasound". In the last decade, this technique has been implemented in various medical fields, particularly family medicine and in emergency and urgent care.Methodology: A descriptive, cross-sectional observational study was conducted, involving a survey of physicians (mostly pediatricians) who had attended a training course in pediatric point-of-care ultrasound organized by different scientific societies. The aim was to obtain feedback from the pediatricians on the use, usefulness, barriers and training in ultrasound.Results: A total of 126 physicians were interviewed, most of whom declared having access to ultrasound. However, less than half of them made use of such devices, due to considerable difficulties, including lack of time and training. A total of 96.8% of those surveyed considered that ultrasound should be part of the training protocol of physicians specializing in pediatrics. The vast majority believed ultrasound training to be very important but considered their level of experience with the technique to be basic.Discussion: The implementation of point-of-care ultrasound in pediatrics is still limited in Spain, though the professionals agree on highlighting its relevance in daily practice. Among the most prominent benefits are resource optimization and shortening of the time to diagnosis. The participants agree that competence in the technique should be incorporated in a structured manner to the training of physicians specializing in pediatrics.